Sosialisasi Terkait Kepercayaan Diri pada Remaja di Panti Pelayanan Sosial Anak Taruna Yodha Sukoharjo - Desy Rosiana; Dhian Riskiana Putri (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Adolescence is a transition period from childhood to adulthood marked by various physical, emotional, and social changes. One of the main challenges faced by adolescents is a lack of self-confidence, which can hinder the development of self-potential and social interaction. Based on observations at the Taruna Yodha Sukoharjo Children's Social Service Center, it was found that many adolescents showed an inferior attitude, were afraid of being wrong, and were reluctant to express their opinions in public. Therefore, this community service aims to increase awareness of the importance of self-confidence through interactive socialization. The implementation method includes four stages, namely the presentation of material on the concept of self-confidence, discussion of personal experiences, providing positive affirmations, and ice breaking to build familiarity. This activity was attended by most of the adolescents at the center and succeeded in increasing active participation from 20% to 50%. Although there were still obstacles such as limited time and the difficulty of some participants in expressing themselves verbally, the evaluation results showed an increase in social interaction and enthusiasm in implementing positive affirmations. This activity proves that an interactive approach can be an effective solution in fostering adolescent self-confidence. For more optimal results, ongoing programs such as public speaking training and psychological assistance are needed. It is hoped that teenagers in the shelter can continue to develop their potential and face social challenges with more confidence.